Pemanfaatan Gliserol Produk Samping Biodiesel Menjadi Triacetin Melalui Proses Esterifikasi Menggunakan Katalis Fly Ash - Nur Khairiati; Zuchra Helwani; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Glycerol is a by-product of biodiesel that produced 10% of the total volume of biodiesel products. Glycerol can be processed into economic product such as triacetin . Triacetin made by estherification process of glycerol and acetic acid with the aid of flya ash as catalyst. This study aims to determine the characteristics of the catalyst fly ash and determine the influence of process variables (concentration of catalyst, reactant mole ratios and estherification time) on glycerol conversion. Catalyst concentration used were 1%, 2% and 3%. The mole ratio of glycerol: Acetic acid were 1:5, 1:7 and 1:9. Estherification time used were 1. 2 and 3 hours. Characteristic of fly ash catalyst such as surface area, the acidity and degree of crystallinity increased after activation. The highest conversion obtained was 53,33% at the operating conditions of catalyst concentration 3%, the mole ratio of reactant 1:9 and estherification time 3 hours. The increasing of catalyst concentration, mole ratio of reactant and estherification time increased the conversion of glycerol.Keywords: biodiesel, estherification, fly ash, glycerol, triacetin.